The correlation between job satisfaction, compensation, and work environment on nurse's turnover intention in Kotamobagu Regional General Hospital using Structural Equation Modeling path analysis - Echa Effendy Siswanto Amir; Eko Winarto; Rita Dewi Sunarno; Shindi Hapsari (GHMJ (Global Health Management Journal), 2023)
Background: Turnover intention is the tendency of employees to leave the organization or resign voluntarily from their job. Several factors that might influence turnover intention are included job satisfaction, work environment, and compensation. Aims: This study aimed to determine the Path Analysis of the effect of job satisfaction, compensation, and work environment on the turnover intention of nurses at Kotamobagu Regional General Hospitals. Methods: A total of 34 nurses (total sampling method) contributed in this cross-sectional study. The model is presented with a single-directed arrow indicating cause and effect. The regression weights predicted by the model are compared with the correlation matrix from the observed data and then the goodness of fit is calculated. This study uses data analysis that is adapted to the research pattern and the variables studied. A causal model was employed, and to test the proposed hypothesis the SEM analytical technique (Structural Equation Modeling) was operated through the AMOS program. Results: From the statistical analysis, the study shows a significant relationship between job satisfaction and turnover intention (p-value = 0.011), and between the compensation and the turnover intention (p-value = 0.026). However, we found that there was no relationship between work environment and turnover intention among the nurses at Kotamobagu Regional General Hospitals (p-value = 0.935).   Conclusion: This study concluded that there is a correlation between work satisfaction and compensation on turnover intention (direct factor), but there was no correlation between work environment on turnover intention (mediator). It is suggested a need to arrange regular evaluation in terms of job satisfaction and compensation to prevent turnover among the nurses.